ISU-ISU NILAI SOSIAL ENTITAS BUDAYA DALAM PUISI â€œKAMUS KECILâ€ KARYA JOKO PINURBO - Nugraha, Via; Pramon, Dede Heri (EDUTECH CONSULTANT, 2019)
This article attempts to describe literary discourse as an alternative answer to cultural problems. This research is based on the discourse of the literary entity's discourse that has not been completed until now. Literary boundaries that have not yet obtained conclusions, precisely literary discourse has developed from various angles such as whatpadd cyber literature and literature. Literature is inseparable from cultural elements. Therefore this study uses literary objects as a point of view as an alternative solution amid the inequality of critics in responding to problems. The result states that the study of cultural problems can be through literature as its object. This can be another alternative besides a sociocultural or holistic approach.